The Relationship Between Physical Activity, Body Image, and Self-Esteem Among High School Students in Makassar - Hezron Alhim Dos Santos; Muhammad Ivan Miftahul Aziz; Maria Herlinda Dos Santos (Lembaga Bale Literasi, 2025)
Adolescence is a critical period in psychological development characterized by physical and social changes and the formation of self-identity. During this phase, physical activity, body image, and self-esteem are interrelated factors that play a role in determining students’ psychological well-being. This study aims to analyze the relationship between physical activity, body image, and self-esteem and to examine the role of body image as a mediating variable. This study employs a quantitative approach with a cross-sectional design. The sample consists of 400 high school students in Makassar City selected using proportionate stratified random sampling. Data were collected using the International Physical Activity Questionnaire-Short Form (IPAQ-SF), the Body Esteem Scale for Adolescents and Adults (BESAA), and the Rosenberg Self-Esteem Scale (RSES). Data analysis was conducted using Pearson’s correlation and regression analysis with bootstrapping mediation testing. The results of the study indicate that physical activity is positively associated with body image (r = 0.489; p < 0.01) and self-esteem (r = 0.421; p < 0.01). Body image is also positively associated with self-esteem (r = 0.597; p < 0.01). Furthermore, body image was found to act as a partial mediator in the relationship between physical activity and self-esteem, with a significant indirect effect (? = 0.224; p < 0.001). In conclusion, physical activity contributes to improved body image and self-esteem among students, both directly and indirectly through body image as a mediator. These findings underscore the importance of physical activity in supporting adolescents’ psychological health in the school setting.